2019
DOI: 10.3766/jaaa.17122
|View full text |Cite
|
Sign up to set email alerts
|

Dizziness, Vertigo, and Mental Health Comorbidity in Gulf War Veterans

Abstract: Gulf War Illness (GWI) is a chronic condition involving symptoms across multiple body systems. Previous research has implicated the vestibular system as a potential underlying factor in the symptoms experienced by veterans with GWI, due in part to exposure to potentially ototoxic chemicals and events.To characterize the presence of vertigo and dizziness symptoms in a sample of veterans with GWI using validated self-report instruments, accounting for mental health comorbidities.This is a case series, follow-up,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…show a VSS baseline score about 14, while our VSS baseline mean is 32.9. The VSS threshold (>12) suggests “severe dizziness” in other studies (Fox et al., 2019 ; Wilhelmsen et al., 2008 ). The baseline score of PHQ‐9 is about 5 in the study from van Vugt et al.…”
Section: Discussionmentioning
confidence: 62%
“…show a VSS baseline score about 14, while our VSS baseline mean is 32.9. The VSS threshold (>12) suggests “severe dizziness” in other studies (Fox et al., 2019 ; Wilhelmsen et al., 2008 ). The baseline score of PHQ‐9 is about 5 in the study from van Vugt et al.…”
Section: Discussionmentioning
confidence: 62%
“…Taken together, except the observation of greater PAG volume in veterans, the patterns of smaller volume in the gross brainstem and impaired brainstem tracts are anatomically consistent with the autonomic nervous system that centrally controls body energy, sleep, pain management, and many neurological regulations. Several studies have suggested that dysregulation of the autonomic nervous system is a common feature in GWI (Fox et al, 2019;Martinez-Lavin and Tejada-Ruiz, 2020;Avery et al, 2021). Hence, our findings could suggest that the presence of CMI in veterans deployed to both Gulf War and Iraq/Afghanistan conflicts is highly relevant to structural alterations in the brainstem.…”
Section: Structural Alterations Of the Brainstem In Veterans With CMImentioning
confidence: 57%